Topics on the dynamics of civil structures, volume 1 : proceedings of the 30th IMAC, a conference on structural dynamics, 2012 - Caicedo, J.M (Conference Proceedings of the Society for Experimental Mechanics Series, 2012)
Topics on the Dynamics of Civil Structures, Volume 1, Proceedings of the 30th IMAC, A Conference and Exposition on Structural Dynamics, 2012, the first volume of six from the Conference, brings together 45 contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: Human Induced Vibrations Bridge Dynamics Operational Modal Analysis Experimental Techniques and Modeling for Civil Structures System Identification for Civil Structures Method and Technologies for Bridge Monitoring Damage Detection for Civil Structures Structural Modeling Vibration Control Method and Approaches for Civil Structures Modal Testing of Civil Structures